Il legamento artificiale: dal tutore intrarticolare al sostituto biomimetico - Manfreda, F.; Tei, M.; Placella, G.; Caraffa, A.; Cerulli, G. (Lo Scalpello - Journal, 2019)
THE ARTIFICIAL LIGAMENT: FROM INTRARTICULAR BRACE TO BIOMIMETIC SUBSTITUTEIn ACL reconstruction, the search for the ideal transplant still finds too many controversies. The choice of surgeons hasalways turned towards the biological solution. The history of artificial ligaments has shown continuous failures. LARSis the most successful synthetic graft in recent years but it should be considered as an “intra-articular brace” andshould be reserved only to specific indications. Currently, the research is focusing on the “bioactive” ligament: newtreatments of terephthalate, in fact, could make these ligaments able to become future biological-like ligaments,overcoming all the limitations of artificial graft.